x= 1

step-by-step explanation: convert 5\frac{11}{12}5

12

11

to improper fraction. use this rule: a \frac{b}{c}=\frac{ac+b}{c}a

c

b

=

c

ac+b

3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{5\times 12+11}{12}3.25+0.5x+1

3

1

+

6

5

x=

12

5×12+11

2 simplify 5\times 125×12 to 6060

3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{60+11}{12}3.25+0.5x+1

3

1

+

6

5

x=

12

60+11

3 simplify 60+1160+11 to 7171

3.25+0.5x+1\frac{1}{3}+\frac{5}{6}x=\frac{71}{12}3.25+0.5x+1

3

1

+

6

5

x=

12

71

4 simplify \frac{5}{6}x

6

5

x to \frac{5x}{6}

6

5x

3.25+0.5x+1\frac{1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+1

3

1

+

6

5x

=

12

71

5 convert 1\frac{1}{3}1

3

1

to improper fraction. use this rule: a \frac{b}{c}=\frac{ac+b}{c}a

c

b

=

c

ac+b

3.25+0.5x+\frac{1\times 3+1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+

3

1×3+1

+

6

5x

=

12

71

6 simplify 1\times 31×3 to 33

3.25+0.5x+\frac{3+1}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+

3

3+1

+

6

5x

=

12

71

7 simplify 3+13+1 to 44

3.25+0.5x+\frac{4}{3}+\frac{5x}{6}=\frac{71}{12}3.25+0.5x+

3

4

+

6

5x

=

12

71

8 simplify 3.25+0.5x+\frac{4}{3}+\frac{5x}{6}3.25+0.5x+

3

4

+

6

5x

to \frac{13.75}{3}+\frac{4x}{3}

3

13.75

+

3

4x

\frac{13.75}{3}+\frac{4x}{3}=\frac{71}{12}

3

13.75

+

3

4x

=

12

71

9 simplify \frac{13.75}{3}

3

13.75

to 4.5833334.583333

4.583333+\frac{4x}{3}=\frac{71}{12}4.583333+

3

4x

=

12

71

10 subtract 4.5833334.583333 from both sides

\frac{4x}{3}=\frac{71}{12}-4.583333

3

4x

=

12

71

−4.583333

11 simplify \frac{71}{12}-4.583333

12

71

−4.583333 to \frac{4}{3}

3

4

\frac{4x}{3}=\frac{4}{3}

3

4x

=

3

4

12 multiply both sides by 33

4x=\frac{4}{3}\times 34x=

3

4

×3

13 simplify \frac{4}{3}\times 3

3

4

×3 to \frac{12}{3}

3

12

4x=\frac{12}{3}4x=

3

12

14 simplify \frac{12}{3}

3

12

to 44

4x=44x=4

15 divide both sides by 44

x=1